Pain Perception, Knowledge, Attitude, and Diet Diversity in Patients Undergoing Fixed Orthodontic Treatment: A Pilot Study - Mok E-Vien; Ummi Sofia Binti Abdul Rahman; Snigdha Misra; Kirti Saxena (Galenos Yayinevi, 2024)
Objective: This study aimed to determine the correlation between pain perception and knowledge, attitude, and diet diversity in patients undergoing fixed orthodontic treatment. Methods: A total of 103 patients (15-40 yrs.; 67 females, 36 males) undergoing orthodontic treatment with a 0.022-inch slot (MBT prescription) in both arches were recruited. Information on pain perception, knowledge, attitude, and diet diversity scores was collected through validated questionnaires using visual analogue scale and close-ended questions at one time point. The correlation between variables was analyzed using the Pearson's correlation coefficient. Results: Of the patients, 48.5% were aged 15 to 19 years old, with 65% females and 73.8% of Chinese ethnicity. Approximately 90% of the orthodontic patients perceived low levels of pain from orthodontic treatment, and 98% had a positive attitude toward orthodontic treatment. The patients had a good level of knowledge (Mean: 6±0.65). Approximately 49.5% of patients reported having moderate diet diversity. No significant correlation was found between pain perception and knowledge, or pain perception and diet diversity (r=0.062, p=0.534). However, a significant weak negative correlation (r=-0.289, p<0.05) between pain perception and attitude was observed. Conclusion: Patients undergoing fixed orthodontic treatment presented with overall low pain perception, a positive attitude, and good knowledge about their treatment with moderate diet diversity. Informing the patient in advance about different orthodontic procedures encourages a positive attitude and facilitates patient cooperation. An interprofessional approach involving nutritionists can provide a holistic patient approach during orthodontic treatment.